Methodology and applications of acousto-electric analogy in photoacoustic cell design for trace gas analysis - Xiaoli Liu; Hongpeng Wu; Lei Dong (Photoacoustics, 2023)
Photoacoustic cells play an important role in photoacoustic trace gas analysis, as they can amplify the photoacoustic signal and improve detection limit. Therefore, the structure and dimensional design of a photoacoustic cell are very important for the performance of a photoacoustic sensing system. In this review, the theory and the method of acousto-electric analogy for the photoacoustic cell design are discussed in detail. Starting from the basics of the acousto-electric analogy, the counterparts of acoustic elements in electric circuits are first deduced from the analogies between acoustic and electric networks. Subsequently, an acoustic transmission line model is reviewed, and the model is demonstrated to optimize the geometry of the photoacoustic cell and investigate the properties of the cell. Finally, using the acousto-electric analogy method, the equivalent electric circuits of several types of photoacoustic cells, such as the Helmholtz resonant photoacoustic cell, the H-type resonant photoacoustic cell, the differential photoacoustic cell, etc., are presented.